A tale of two intensive care units (ICUs): Baseline Staphylococcus aureus colonization and mupirocin susceptibility in neonatal and pediatric patients requiring intensive care. (22nd March 2023) - Arora, Harbir S.; Khan, Humera; Ailumerab, Haider; Natarajan, Girija; Meert, Kathleen; Salimnia, Hussein; Valentini, Rudolph; Thomas, Ronald; Semproch, Lynn; Asmar, Basim I.; McGrath, Eric J.
Abstract: Objective: To assess the incidence rate of S. aureus colonization at baseline along with the mupirocin susceptibility (or resistance) rate in patients in a neonatal intensive care unit (NICU) and a pediatric intensive care unit (PICU) in conjunction with the implementation of universal decolonization as the standard of care. Design: Prospective cohort study. Setting: Children's Hospital of Michigan (CHM) inpatient intensive care units (ICUs). Participants: Newly admitted pediatric patients to the CHM NICU or PICU aged between 1 day and ≤21 years. Interventions: Baseline and follow-up S. aureus screening cultures were obtained before patients underwent universal decolonization with mupirocin 2% antibiotic ointment (intranasal and umbilical) and chlorhexidine baths as standard of care to reduce CLABSI rates. Results: Baseline S. aureus colonization rates of new admissions to the CHM NICU and PICU were high at 32% and 29%, respectively. Baseline mupirocin susceptibility to any S. aureus growth was 98.4%. All baseline culture isolates whether positive for MRSA or MSSA, with one exception, had minimum inhibitory concentrations (MICs) of ≤0.19 µg/mL. All follow-up study cultures after universal decolonization at 7 days or beyond with any S. aureus growth had mupirocin MICs of ≤0.125 µg/mL. Conclusions: Baseline S. aureus colonization rates of new admissions to the CHM ICUs were high as was baseline mupirocin susceptibility. Follow-up cultures, albeit limited in number, did not detect increasing mupirocin MICs over 1 year, despite broad mupirocin exposure due to the implementation of universal decolonization.